Prevalence and factors associated with tobacco use among adults attending selected healthcare facilities in Buffalo City Metropolitan Municipality, South Africa - E O Owolabi; D T Goon; O V Adeniyi; E Seekoe; A O Adedokun (South African Family Practice)
Aim: Tobacco use increases the risk of cardiovascular disease, premature death and certain cancers. This study investigated the prevalence and determinants of tobacco use among adults in Buffalo City Metropolitan Municipality (BCMM), South Africa.